Downregulation of SOCS gene expression can inhibit the formation of acute and persistent BDV infections. (21st October 2020) - Li, Xuejiao; Xia, Qing; Meng, Caiyun; Wu, Hao; Huang, He; Qian, Jun; Li, Aimei; Zhai, Aixia; Kao, Wenping; Song, Wuqi; Zhang, Fengmin
Abstract: High expression of suppressors of cytokine signalling (SOCS) has been detected during various viral infections. As a negative feedback regulator, SOCS participates in the regulation of multiple signalling pathways. In this study, to study the related mechanism between SOCS and BDV and to explore the effect of SOCS on IFN pathways in nerve cells, downregulated of SOCS1/3 in oligodendroglial (OL) cells and OL cells persistently infected with BDV (OL/BDV) were constructed with RNA interference technology. An interferon inducer (poly I:C, PIC) and an IFN‐α/β R1 antibody were used as stimulation in the SOCS1/3 low‐expression cell models, qRT‐PCR was used to detect type I IFN and BDV nucleic acid expression, Western blot was used to detect the expression of BDV P40 protein. After BDV acute infection with OL cells which with downregulated SOCS expression, the virus accounting was not detected, and the viral protein expression was lower than that of OL/BDV cells; the OL/BDV cells with downregulated SOCS expression had lower virus nucleic acid and protein expression than OL/BDV cells. Stimulated by IFN‐α/β R1 antibody, the expression of type I interferon in OL/BDV cells decreased, and the content of BDV nucleic acid and protein increased, which was higher than that of OL/BDV cells. From the results, it was concluded that downregulating SOCS1/3 can inhibit the formation of acute BDV infection and virus replication in persistent BDV infection by promoting the expression of IFN‐α/β and that SOCS can be used as a new target for antiviral therapy.